For the gods of Girsu : city-state formation in ancient Sumer - Rey, Sébastien, 1981- (Archaeopress, 2016)
This work demonstrates Girsu is a primary locale for re-analyzing, through an interdisciplinary approach combining archaeological and textual evidence, the origins of the Sumerian city-state.